ChallengingUntouchbility: Dalit Intitiative and Experience From Karnataka - Charsely,Simon R.; Karanth,G.K (Sage, 1998)
The contributors to this volume describe the status of rural untouchable castes and study their efforts to challenge the daily humiliations they face.